Frequency of Factor V Deficiency (F5d) among patients with Bleeding Complaints - Noor-Ul-Ain Aziz, Qurat-Ul-Ain Qureshi, Sidra Kadir, Maleeha, Noureen Abbasi, Ikram Din Ujjan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Commonest genetic defect includes mutation of F5 gene on the long arm of chromosome1q23 thus both parents carry defective gene. Aim: To evaluate the frequency of inherited Factor V deficiency among patients presenting with bleeding at T.C hospital. Study design: Cross sectional study. Methodology: A total of 300 patient presented with complain of bleeding were included in this study. Detailed history was noted. PCR was performed. After preparation of PCR reaction mixture, incubate tubes into thermal cycler having specific cycling condition. Primer was use for both PCR amplifications and sequencing reactions was designed. Applied bio-system was used for mutation detection. The collected data was analyzed by using SPSS version 25. Results: The average age of the patients was 36.87±9.40 years. There were 213(71%) male and 87(29%) female. Frequency of inherited factor V deficiency in patients presented with complains of bleeding was 3.33% (10/300). Conclusion: It was concluded that frequency of inherited factor V deficiency in present study was low. Conclusion: frequency of inherited factor V deficiency in present study was low (3.33%).